2018
DOI: 10.1051/matecconf/201823403006
|View full text |Cite
|
Sign up to set email alerts
|

Automotive compressor: effect of an electric throttle in the upstream circuit on the surge limit

Abstract: On vehicles equipped with a turbocharged engine, there is a risk of compressor surge. This surge generates instabilities that lead to driving inconvenience, or even mechanical failure of the supercharging system. In general, the surge appears rather in transient operation: sudden closing of the throttle valve on gasoline engine, regulation of the EGR on diesel engine linked also to turbine regulation (VNT device or Waste Gate). On a turbocharger test stand, we set up the surge line in a “conventional way”: sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, this limit is not reliable once the turbocharger is coupled to the engine, because surge appearance is affected by the piping geometry around the compressor [19][20][21][22][23][24] and engine pulsation [25,26], as stated before. Besides, the surge margin may be modified under transient flow conditions [29]. Instead, the compressor outlet pressure (p 2 ) signal, acquired with a sampling of 0.2 crank-angle degrees, and its first derivative were used for surge detection.…”
Section: Surge Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this limit is not reliable once the turbocharger is coupled to the engine, because surge appearance is affected by the piping geometry around the compressor [19][20][21][22][23][24] and engine pulsation [25,26], as stated before. Besides, the surge margin may be modified under transient flow conditions [29]. Instead, the compressor outlet pressure (p 2 ) signal, acquired with a sampling of 0.2 crank-angle degrees, and its first derivative were used for surge detection.…”
Section: Surge Detectionmentioning
confidence: 99%
“…The following two strategies were studied: the optimization of throttle closure and the application of different closings on the intake flap, located upstream of the compressor, to increase EGR rate. Podevin et al [29] already demonstrated, via experiments in a turbocharger test rig, that the surge area can be decreased by up to 60% by applying a certain closing on an electric throttle at the compressor inlet. In order to evaluate both strategies, a series of tip-outs under the most critical surge conditions was tested, and the filtered crank-angle resolved pressure signal at the compressor outlet and its time derivative were analyzed for surge detection.…”
Section: Introductionmentioning
confidence: 99%